NGINEP CALON MANTU (ASA, 2021)
g praduga buruk akan berdampak pada fitnah yang tidak-tidak ABSTRACTA procession to bind a relationship is actually not a problem, in fact this is encouraged, but what becomes a problem is a custom that requires a bridegroom to stay at the bride's house before carrying out the marriage contract, with the aim that between two families can establish a closer relationship, one example of such a custom,  namely the 3-day Pulang custom in the Bondowoso area which requires the bride-to-be husband to stay at the bride's house for three days, then after three days the prospective bride and groom are delivered to her home again by the family of the woman as well as holding a proposal event.In this paper, there are at least two formulations of the problem, how is the procedure for prayer in the perspective of Islamic law and positive law ?, how is the law of "Pulang 3 days" perspective of Islamic law ?.The method used in writing this scientific paper uses a literature review where the author will read in full and widely on various primary sources to obtain appropriate data. Based on this formulation, it can be concluded that, the procedures for inviting women recommended by the Islamic perspective are as follows, preaching before performing a prayer or prayer, starting the khodbah with hamdalah or praise to Allah, fighting and saying greetings to the Prophet Muhammad Saw, praying to always be devoted to Allah, conveying the purpose of coming to ask, such as "the purpose of me coming to this place is to propose to your daughter". The prespetuary system of positive law is not explained because positive law respects and respects the applicable customary law, so that customary law works as a decisive custom, not a provision of the state. With this, we can draw a common thread that the 3-day Pulang custom that has been carried out by the Bondowoso tribe cannot be said to be true under Islamic law or just say that the law is haram, for many reasons to prohibit this, such as when the male candidate and the future woman are left alone in the room for 3 days, it is possible that the male shahwat will wake up at that time and will lead to adultery,  Then if you don't do anything, the emergence of bad presumptions that arise from people with presumptions of not having done a marriage contract can already sleep together this needs to be avoided, because the ends of bad presumptions will have an impact on slander that is no-no.
Keywords: In Islam, Seserahan In Positive Law, Seserahan In Islamic Perspective Law